Usuń nawiasy i wykonaj redukcję wyrazów podobnych.
a)4c-(3c+2)-10
b)7x-8-(5x+6)
c)9y-(8-3y)+16
d)5x-(2-4x)+8x-7
e)-(-5c-8)+6-9c-c
f)-4(3x-6)-3(2+7x)
g)5(3z-7)-9(-8z-6)
h)-3(5x-4)+8(-3z+2)
i)7x-3(5x+2)-6(7+2x)
j)-5(3y-7)-2(6+4y)+3y







zadanie 2.

zamień iloczyn na sumę
a) 3(x-3),5(y+z),4(3x-y),3(4a-c),-2(7-4n)
b)jedna druga (4z+2),-jedna trzecia(6b-3), 0,2(x-5y), 3(jedna trzecia a+1)

2

Odpowiedzi

2010-03-06T20:32:44+01:00
A)4c-3c-2-10=c-(-12)=c+12
b)7x-8-5x-6=2x-2
c)9y-8+3y+16=12y+8
d)5x-2+4x+8x-7=17x-9
e)5c+8+6-9c-c=-5c+14
f)-12x+24-6-21x=-33x+18
g)15z-35+72z+54=-19+87z
h)-15x+12-24z+16=-39z+28
i)7x+15x-6-42-12x=10x-48
j)-15y+35-12-8y+3y=-20y+23

2
a)3(x-3)=3x-9
5(y+z)=5y+5z
4(3x-y)=12x-4y
3(4a-c)=12a-3c
-2(7-4n)=-14+8n
4 5 4
2010-03-06T20:43:40+01:00
Zad.1
a)4c-(3c+2)-10=4c-3c-2-10=c-12
b)7x-8-(5x+6)=7x-8-5x-6=2x-14
c)9y-(8-3y)+16=9y-8+3y+16=12y+8
d)5x-(2-4x)+8x-7=5x-2+4x+8x-7=17x-9
e)-(-5c-8)+6-9c-c=5c+8+6-9c-c=-5c+14
f)-4(3x-6)-3(2+7x)=-12x+24-6-21x=-33x+18
g)5(3z-7)-9(-8z-6)=15z-35+72z+54=87z+19
h)-3(5x-4)+8(-3z+2)=-15x+20-24z+16=-15x-24z+36
i)7x-3(5x+2)-6(7+2x)=7x-15x-6-42-12x=-20x-48
j)-5(3y-7)-2(6+4y)+3y=-15y+35-12-8y+3y=-20y+23

zad.2
a)3(x-3)=3x-9=-(-3x+9)
5(y+z)=5y+5z
4(3x-y)=12x-4y=-(-12x+4y)
3(4a-c)=12a-3c=-(-12a+3c)
-2(7-4n)-14+8n

b)1/2(4z+2)=2z+1
1/3(6b-3)=2b-1=-(-2b+1)
0,2(x-5y)=0,2x-y=-(-0,2x+y)
3(1/3a+1)=a+3